A method for distinguishing the sex of the oil-sardine, Sardinella longiceps Val. in the field - George, K C (Indian Journal of Fisheries, 2016)
Sex studies form an important part of fishery biological investigations and as such easy methods of distinguishing the sexes of commercially important fishes will lighten the work of determining their sex. Well-known examples of conspicuous secondary sexual characters are found in some of the cyprinids and cyprinodonts (Norman, 1957) and such characters help us to distinguish the sexes of those fishes easily. In many teleosts the genital and urinary pores open on a more or less prominent papilla. Among the clupeoids, O'Connell (1955) makes mention of a median muscular ridge in Sardinops ccerulea, extending from the rectal portion of the intestine and bearing the genital and urinary pores. He terms this ridge, as urogenital papilla. There is no indication of the sex of the fish in which such a papilla has been observed. Determination of the sex in clupeoid fishes have almost always been done by dissection and examination of the gonads. But, while studying the sex composition and maturity of the oil-sardine, Sardinella longiceps, the presence of a muscular papilla bearing the genital and urinary pores has been observed in the male and a membranous one in the female. On the basis of those characters the fish can be sorted out into the two sexes without actual dissection.